Unacceptable gender discrimination of the pro homine principle in health and the sub-rules of its application - Goyes Moreno, Isabel; Hidalgo Oviedo, Mónica (Universidad y Salud, 2015)
The obligation to ensure gender equality is not a merely legal issue. On the contrary, it is a social need that is the responsibility of all disciplines. The health sciences and law need to understand and engage with such a mandate, so one of the new statutory law of health principles (pro homine) is patriarchal, as long as it maintains a male language over the feminine one. The novelty and importance of this article lies in the reflection on the guiding character that the mentioned law is called to meet in the coming years and in the international commitments of the Colombian State with gender equality. Only the general understanding that the principle "pro homine", which should be understood as the principle "pro person", will prevent discriminatory factors in a health system in which there are still exclusions, and with the help of the jurisprudence sub-rules, it will enable an application in favor of the right to health of all people.